Integrating Local Wisdom in Reading Literacy Assessment Through Teachmint: A Book Development Initiative - Diana, Purwati Zisca; Wijayanti, Dedi; Hermanto, Hermanto; Fujiastuti, Ariesty (JOLLT Journal of Languages and Language Teaching, 2025)
This qualitative case study, conducted in West Manggarai, East Nusa Tenggara, employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) to address the persistent issue of cultural disconnect in Indonesia’s standardized reading literacy assessments. The study aimed to develop and evaluate a reading literacy Minimum Competency Assessment (MCA) book that integrates local wisdom and is supported by the Teachmint app as an interactive learning platform. The intervention contextualized assessment materials by incorporating local folklore, customs, and socio-cultural environments into the design of learning content. Validation by experts rated the book as highly feasible (91.2%), with strong positive responses from both teachers (88.5%) and students (85%). Implementation of Teachmint enhanced accessibility, motivation, and engagement through digital features like quizzes, automatic feedback, and interactive discussions. Quantitative findings revealed significant gains in students’ informational text comprehension (30.03%), literary text comprehension (11.92%), and critical analysis skills (35.09%). A comparative study also demonstrated that students assessed through Teachmint outperformed those using conventional platforms like Google Forms. This research highlights the effectiveness of integrating local cultural contexts and educational technology to enhance reading literacy and offers practical insights for developing culturally responsive assessments in Indonesia.